Searches for third-generation scalar leptoquarks in root s=13 TeV pp collisions with the ATLAS detector - Çetin, Serkant Ali (SPRINGER, 2019)
Limits are set on the pair production of scalar leptoquarks, where all possible decays of the leptoquark into a quark (t, b) and a lepton (, ) of the third generation are considered. The limits are presented as a function of the leptoquark mass and the branching ratio into charged leptons for up-type (LQ<sub ) and down-type (/t) leptoquarks. Many results are reinterpretations of previously published ATLAS searches. In all cases, LHC proton-proton collision data at a centre-of-mass energy of = 13 TeV recorded by the ATLAS detector in 2015 and 2016 are used, corresponding to an integrated luminosity of 36.1 fb(-1). Masses below 800 GeV are excluded for both LQu and LQd independently of the branching ratio, with masses below about 1 TeV being excluded for the limiting cases of branching ratios equal to zero or unity.
Keywords: Hadron-Hadron scattering (experiments)